Application of high‐frequency ultrasound in esophageal atresia with distal fistula. Issue 4 (27th August 2013) - Su, P.; Yuan, Y.; Zhang, Z.; Huang, Y.; Wang, W.
Summary The present study was designed to evaluate the accuracy of preoperative ultrasonography (US) in depicting the structure of esophageal atresia with distal fistula (EA‐DF) and to determine its role in planning the surgical strategy by digitally measuring the interpouch distance (ID). Thirty‐six neonates (20 males and 16 females) born with EA‐DF were included in this study. After obtaining chest radiographs of the neonates with a coiled nasogastric tube in the upper esophageal pouch, longitudinal esophageal high‐frequency US was performed. The esophageal structures were displayed, and the IDs measured on US images were compared with the surgical findings. With the use of US, the structure of EA‐DF was accurately depicted, and the ID detected by US correlated well with the surgical findings. Statistical analysis demonstrated no significant difference in the ID as assessed by US and surgery (R = 0.99, P < 0.001).). US findings were crucial for planning the surgical strategy in 9 (25.0%) patients. Preoperative US could provide more accurate information on the structure of EA‐DF and play a crucial role in planning the surgical strategy.